Atomic layer deposition of perovskites part 2: Designing next generation electronic applications. Issue 1 (25th December 2019) - Bin Afif, Abdulla; Dadlani, Anup L.; Burgmann, Stephanie; Köllensperger, Peter; Torgersen, Jan
Abstract: From part one, we learned that perovskites are interesting materials with tunable properties. Here, four current applications are elaborated on; high‐κ dielectrics, piezoelectrics, optoelectronics, and solar to energy conversion devices. To start with, we discuss perovskite based dynamic random‐access memory (DRAM) capacitors, where ALD strontium titanate (STO) of thickness 10 nm can achieve dielectric constants (k) of up to 146. Next, we discuss ALD perovskite piezoelectric‐based device design of nanoelectromechanical systems (NEMS) and microelectromechanical systems (MEMS). There is a renewed interest in barium‐based ternary compounds which have piezoelectric coefficients up to 500 pC/ N. We further explore ALD perovskite‐based solar photovoltaics (PVs), where conformal and uniform layers of lead sulfide (PbS) absorbing layers allow deposition on large surfaces, facilitating perovskite architectures with conversion efficiency reaching 20%. Finally, we learn how lanthanum‐based perovskites can replace cerium oxide, which is currently utilized for thermo‐chemical processes for solar to energy conversion. Subsequently, we discuss different characterization techniques allowing us to deepen our understanding of process property relationships eventually leading to further performance enhancements.